Bridging the Digital Divide: Management of Platform Merdeka Mengajar for Self-Regulated Teacher Profes-sional Development in Remote Elementary Schools - Listia Rismayanti (Journal of Science and Education (JSE), 2026)
The implementation of the Merdeka Curriculum in Indonesia necessitates a paradigm shift in teacher professional development towards digital self-regulated learning. This study investigates the management of the Platform Merdeka Mengajar (PMM) as a strategic instrument for enhancing the academic capacity of elementary school teachers, specifically within the technological constraints of SDN Girimukti and SDN Pacet 1, West Java. Employing a qualitative case study design, data were harvested through participant observation, in-depth interviews, and document analysis. The findings reveal a tripartite management mechanism: (1) Adaptive Planning and Structural Organization, where school leadership navigates infrastructural scarcity through resource mapping and the appointment of digital champions; (2) Implementation Dynamics, characterized by peer-scaffolding models and hybrid online-offline learning strategies to overcome connectivity barriers; and (3) Surveillance and Evaluative Feedback, where the principal transitions from an administrator to a digital pedagogical supervisor. The study concludes that while digital infrastructure is a prerequisite, the management of human resources—specifically the principal's active leadership and the cultivation of a collaborative learning culture—is the decisive factor in the successful adoption of PMM. These findings challenge the technological determinism view, suggesting that managerial agility can mitigate infrastructural deficits in educational transformation.